Effect of platelet rich plasma (prp) to autogenous bone graft - Saputro, Iswinarno Doso; Hutagalung, Magda Rosalina; Wahdini, Siti Isya (Folia Medica Indonesiana, 2017)
Bone graft use in maxillofacial surgery is currently developing, though some problems still persist. One of promising solutions to the problems is application of platelet rich plasma which may accelerate soft tissue healing and bone formation. This study aims to provide basic understanding to the development of PRP application in bone healing where bone graft is applied on human maxillae. Bone defects were made on maxillae of albino rabbits, with an application of bone graft in control group and bone graft plus PRP in treatment group. Histopathological analysis was performed in both groups to assess osteoblast density and collagen tissue area. On day 21st, more osteoblast density and collagen area in treatment group are significantly observed (p<0.05, 95% confidence interval). Observations were made on hard callus formation. In conclusions, platelet rich plasma may increase density of osteoblast in rabbit maxillary bone graft.